2020
DOI: 10.3991/ijet.v15i21.16537
|View full text |Cite
|
Sign up to set email alerts
|

Enhance Students’ Motivation to Learn Programming Through Projects

Abstract: This article presents the results of a pedagogical experiment when teaching microcontroller programming. The pedagogical experiment was conducted at the Faculty of Information Technology of the L.N. Gumilyov Eurasian National University in the form of project-based seminars on the Arduino platform (2017-2020). The experiment was attended by 88 first-year IT students. Our goal in this study is to verify the proposed hypothesis on the use of the project-based learning method in teaching microcontroller programmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, low-performing students in this study had a positive attitude toward collaboration. erefore, getting students to write code together in pairs or small groups can enhance students' programming performance and confidence [52][53][54]. Pair programming produces more rapid and effective solutions than solo programming [75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low-performing students in this study had a positive attitude toward collaboration. erefore, getting students to write code together in pairs or small groups can enhance students' programming performance and confidence [52][53][54]. Pair programming produces more rapid and effective solutions than solo programming [75].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to motivating the students, instructors should provide novices with fundamental skills and simple problem solving before starting the course so that novices have the background needed to understand basic programming. Previous studies have suggested various teaching methods: live coding, gamification, team based-learning, interactive computer tutors, mentor support, peer instruction, and pair programming [47][48][49][50][51][52][53][54]. However, some of these teaching methods do not always succeed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Communication skills: the ability to communicate and collaborate effectively in virtual environments (Nurbekova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%